OPTIMISATION OF PHARMACY CONTENT IN PAEDIATRIC ONCOLOGY AND HAEMATOLOGY CLINICAL TRIAL PROTOCOLS. EXPERIENCE OF CHEMOTHERAPY PHARMACY ADVISORY SERVICE (CPAS) FROM 2011 TO PRESENT. Issue 9 (17th August 2016) - Greer, Rachel; Harvey, Sally
Abstract : Aim: Clarity and accuracy of the pharmacy aspects of cancer clinical trial protocols is essential. Inconsistencies and ambiguities in protocols have the potential to delay research and jeopardise both patient safety and the collection of credible data. The Chemotherapy and Pharmacy Advisory Service (CPAS) was established in 2007 by the UK National Cancer Research Network, currently known as National Institute for Health Research Clinical Research Network, to improve the quality of pharmacy-related content in cancer clinical trial protocols. This abstract describes the scope of CPAS, its methodology of mandated protocol review and an analysis of the issues found and reported in paediatric oncology and haematology trials. Method: All paediatric oncology and haematology clinical trial protocols from 2011 to present were included in this study. A review checklist was developed by CPAS and used by the review panel, consisting of pharmacists, doctors and nurses, to standardise the evaluation of all protocols. Once completed, all reviews were collated and any queries and inconsistencies were fed back to Chief Investigators and study sponsors. The most common remarks made at protocol review were summarised and categorised through retrospective analysis. It is at the discretion of the study Sponsor and Chief Investigator to accept any recommendations or amendments based on the findings. In order to evaluate the impact of the service, Chief Investigators were asked to respond to queries made at protocol review and make appropriate changes to their protocols. Responses from Chief Investigators have been collated and acceptance rates determined. Results: A total of 13 paediatric protocols were reviewed during this period. The mean number of comments per protocol was 32 and these mainly concerned the drug regimen, support medication, dose calculation, drug information and administration. Eleven of the Chief investigators returned responses to their protocols reviews. All responses were positive with an overall acceptance rate of 82% of the proposed protocol changes. Conclusion: Review by CPAS of pharmacy content of paediatric oncology and haematology clinical trial protocols prior to final approval is feasible and exposes many undetected clinically relevant issues that could hinder efficient trial conduct and/or patient safety. This analysis has highlighted that the majority of suggestions were deemed clinically significant and effectively incorporated into the final protocols. The refinement of existing and development of further pharmacy-related guidance documents by CPAS might support more effective and safer clinical research.